What is normal black African hair? A light and scanning electron-microscopic study. - Khumalo, N; Doe, P; Dawber, R; Ferguson, D (2000)
BACKGROUND: The hair of normal black Africans forms a mat of tightly interwoven hair shafts. The effect of this on the structure of the hair shaft and the response to grooming is unknown. OBJECTIVE: Our purpose was to use light and scanning electron microscopy (SEM) to examine the structure of Negroid-type hairs and effects of combing in black African volunteers. METHODS: Hair samples were collected, by combing, from Africans and compared with those from Caucasian and Asian volunteers. The volunteers had never used chemical treatments. Their hair had not been cut for at least 1 year and grooming had been limited to shampooing, drying, and combing. RESULTS: More than 2000 hairs in 12 African volunteers were examined by light microscopy. The hairs appear as a tight coiled springlike structure. Many shafts exhibited knots (10%-16% vs 0.15%) and appear broken compared with hair shafts from other ethnic groups. SEM of African hairs showed features consistent with repeated breaks of the shaft. Examination of hairs in situ showed interlocking of hair shafts. CONCLUSION: These observations provide an understanding of the physical nature of, and effect of combing on, black African hair.